ANALISIS PENGUNGKAPAN SUSTAINABILITY REPORT PT. WASKITA KARYA (PERSERO) TBK DAN YTL CORPORATION BERHAD TAHUN 2018 BERDASARKAN GRI STANDARDS - Yenny Christine; Carmel Meiden (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2021)
PT Waskita Karya (Persero) Tbk and YTL Corporation Berhad which are in construction sub-industry. In submitting the Sustainability Report that have been published by the two construction companies, GRI Standards to see how far the level of compliance of PT Waskita Karya (Persero) Tbk and YTL Corporation Berhad in including the contents of the sustainability report. This study uses descriptive analysis including Data Collection, Data Recording, Data Analysis and Interpretation. Based on the study and result, that the level of compliance of the general disclosure of sustainability reports from PT Waskita Karya (Persero) Tbk is 84%, which is included in the well applied category. Meanwhile, YTL Corporation Berhad shows a compliance rate of 66%, which is included in the partially applied category. Furthermore, the level of compliance of the disclosure of material topics from PT Waskita Karya (Persero) Tbk is 51% which is included in the partially applied category. Meanwhile, YTL Corporation Berhad level of compliance is is 75% which is included in the partially applied category. Keywords: Sustainability report, level of compliance, economic, environmetal, social, GRI Standards References: Astuti, Feliana, and Wika Harisa Putri. 2019. “Studi Komparasi Kualitas Pengungkapan Laporan Keberlanjutan Perusahaan Konstruksi Dalam Dan Luar Negeri.” 1(40):34–46. doi: 10.20885/ncaf.vol1.art4. Elkington, John. 1997. Cannibals with Forks: The Triple Bottom Line of 21st Century Business. Fahriza, Romi. 2014. “Tingkat Pengungkapan Sustainability Report ( Studi Pada Perusahaan High Profile Di BEI Tahun 2009 – 2013 ).” Freeman, R. Edward. 1984. Strategic Management: A Stakeholder Approach. Frynas, Jedrzej George. 2009. Beyond Corporate Social Responsibility: Oil Multinationals and Social Challenges. GRI. 2016. “GRI 101: Fundamental 2016.” GSBB 1(1):30. Gudono. 2012. Open Library - Teori Organisasi -2/E. Harymawan, Iman, Mohammad Nasih, Melinda Cahyaning Ratri, Soeprajitno, Raden Roro Widya Ningtyas, and Rohami Shafie. 2020. “Sentiment Analysis Trend on Sustainability Reporting in Indonesia: Evidence from Construction Industry by Iman Harymawan, Mohammad Nasih, Melinda Cahyaning Ratri, Raden Roro Widya Ningtyas Soeprajitno, Rohami Shafie.”. Jensen, Michael C., and William H. Meckling. 1976. “Theory of the Firm: Managerial Behavior, Agency Costs and Ownership Structure.” Journal of Financial Economics 3(4):305–60. Jogiyanto, H. .. 2000. Teori Portofolio Dan Analisis Investasi. Edisi 2. BPFE-UGM. Kharima, Bella Putri, and Lies Zulfiati. 2020. “Pengaruh Pengungkapan Sustainability Report Terhadap Nilai Perusahaan (Analisis Lintas Negara Di Indonesia, Malaysia Dan Singapura)/The Influence Of Sustainability Report Disclosure On Firm Value (Cross-Coutry Analysis In Indonesia, Malaysia And Singapor.” Kozlowski, Anika, Cory Searcy, and Michal Bardecki. 2015. “Corporate Sustainability Reporting in the Apparel Industry an Analysis of Indicators Disclosed.” International Journal of Productivity and Performance Management 64(3):377–97. Laan, Sandra Van Der. 2009. “The Role of Theory in Explaining Motivation for Corporate Social Disclosures: Voluntary Disclosures vs ‘ Solicited ’ Disclosures.” Australlasian Business and Finance Journal 3(4):15–30. Lindawati, Ang Swat Lin, and Marsella Eka Puspita. 2015. “Corporate Social Responsibility: Implikasi Stakeholder Dan Legitimacy Gap Dalam Peningkatan Kinerja Perusahaan.” Jurnal Akuntansi Multiparadigma 157–74. Manisa, Dea Eka, and F. Defung. 2017. “Pengaruh Pengungkapan Sustainability Report Terhadap Kinerja Keuangan Perusahaan Infrastruktur Yang Terdaftar Di Bursa Efek Indonesia.” Forum Ekonomi 19(2):174. Muhammad Khafid, Niswah Baroroh, and Tusyanah. 2019. Sustainability Report Tinjauan Teoritis Dan Riset. Nazir, Moh. 2014. Metode Penelitian. Nugroho, Nickochione Antony. 2019. “Analisis Pengungkapan Laporan Keberlanjutan Berdasarkan Topik Spesifik GRI Standards Pada Perusahaan Sektor Konstruksi Tahun 2017 Dan 2018.” (1789). Pertiwi, Faradina Berlian. 2019. “Analisis Komparatif Pengungkapan Laporan Keberlanjutan PT Aneka Tambang Dan PT Indo TambangRaya Megah Tahun 2018 Berdasarkan Global Reporting Initiative (GRI) Standards.” Suwardjono. 2014. Teori Akuntansi Perekayasaan Pelaporan Keuangan Edisi 3. Syahputra, Doni, Herlina Helmy, and Erly Mulyani. 2019. “Analisis Pengungkapan Lingkungan Berdasarkan Global Reporting Initiatives(GRI) G4 (Studi Kasus Pada PT Bukit Asam (Persero) Tbk Dan PT Indo Tambangraya Megah Tbk Tahun 2016-2017).” Jurnal Eksplorasi Akuntansi 678–93. Wirjono, Endang Raino, Universitas Atma, Jaya Yogyakarta, Agus Budi Raharjono, Universitas Atma, and Jaya Yogyakarta. 2019. “Implementasi Aktivitas Kualitas Lingkungan.” 31(1):22–47.